Aristonothos. Il vaso (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2010)
The two scenes representing the blinding of the Cyclops Polyphemus by Odysseus and a naval battle, depicted on each side of the crater of Aristonothos (650 B.C.), found in a tomb of Cerveteri, are usually considered as two paratactic representations of the struggle between two different ethnic groups. This contribution presents a new hypothetical interpretation considering the crater as a visual and aesthetic unity: the two scenes might be read in sequence, one being the consequence of the other. Odysseus, skilled and gifted with intelligence (metis), faces the Cyclops; however his excessive metis upsets the Cyclops' father Poseidon and causes damage and struggle, expressed by the naval battle. At the same time the crab depicted under the handles of the crater, symbol of the right use of skill and intelligence, fits well in this frame.The Aristonothos krater implies its usage in symposia where different ethnic groups could have been involved, shortly after the expansion of the Greeks westwards, in the frame of contacts among Greeks, Phoenicians and Etruscans. Thus the figured scene depicted on the crater might have acted as advice and warning regards the right use of wine.